A pichação como apropriação da cidade: o pixador como formador do cenário urbano - Álan Oziel da Silva Pires (2017)
This present work is a historic look at pixação in Belo Horizonte city and it investigates how this writing way has been developing since 1960s until today. The investigation is not concerned just about the writings on the walls, but it explores the pixação from the relation between the person and city, verifying how the pixo stablishes in this relation. In this way, we understand the city is not just the support to pixo, but its constitutor element, so we analyzed how the pixação appropriates from the city, the speeches and instituted spaces and, from the subversion of them, it constructs its socializing places and memory, making present in the urban scenery. We also investigated the strategies of the formation of memory of pixação and its function in the groups cohesion. For this, we analyzed the followers memory devices of this writing way: sheet (collection of sheets with pixo by many begginers and experienced practitioners), agenda pictures (walls with pixações and different groups registrations), relics (walls with old pixações by authors that do not act anymore), collection of parts of newspapers and magazines about pixo. We tried to evidence the historic groundwork of pixação and put it in a non-agreed writing way in non-conventional supports and also presented a possible way from pichação to pixação, presenting the formal transformation of these writings and the distinction of their names. We also wanted to show the relations of the social dynamic, in political and demographic aspects and the pixo configuration. In this research we approached the pixação as a politic action and asked the understanding of pixação as a simple scrawl, because we realized how it points a choice to appropriate and resignificate the town, not restricting it to youths. To finish, this work possibilities to realize how pichação and pixação change from strategic element in politic confrontation and becomes something with centrality in its making as a political action.